Vaccination rate and immunity of children and adolescents with inflammatory bowel disease or autoimmune hepatitis in Germany. Issue 7 (11th February 2020) - Cagol, Luana; Seitel, Teresa; Ehrenberg, Sarah; Frivolt, Klara; Krahl, Andreas; Lainka, Elke; Gerner, Patrick; Lenhartz, Henning; Vermehren, Jan; Radke, Michael; Trenkel, Stefan; Mayer, Benjamin; et al.
Highlights: Neither vaccination certificate nor history of chicken pox predicts VZV immunity. Insufficient VZV vaccination catch-up in birth cohorts born prior 2005. Better realization of vaccination catch-up by paediatrician than general practitioner. Serologic investigations demonstrate occult immunization of non-immunized patients. Abstract: Background and aims: Immunosuppressed patients are at risk of severe infections with vaccination preventable diseases. We evaluated vaccination rate and immunity of children and adolescents with inflammatory bowel disease (IBD) and autoimmune hepatitis (AIH). Methods: Immunization rate of 329 children with IBD (n = 300) and AIH (n = 29) was assessed in seven German centres using vaccination certificates, history of chicken pox and by determining anti-varicella zoster virus (VZV) and anti-measles IgG antibodies. Results: Of the total cohort 86% received long-term immunosuppression. Four doses of a hexavalent vaccine were documented in 89%, at least one dose of measles, mumps, and rubella (MMR) vaccination was documented in 325 (99%), with 300 (92%) receiving two doses. Anti-measles IgG concentrations were insufficient in 11% of the immunized patients. VZV vaccination was officially recommended in Germany since 2004, and implemented in 88% born from 2005 onwards. In patients born earlier VZV catch up vaccination only reached 25% (n = 67). Of 118 patients with documented VZV vaccination 25 (21%) did not display sufficient anti-VZV IgG. Of 198 patients with a history of chicken pox, six had undetectable anti-VZV IgG. Of 29 patients having neither had chicken pox nor VZV vaccination, 20 were found to have sufficient anti-VZV IgG. Conclusions: In our cohort vaccination coverage for hexavalent and MMR vaccinations was good, but insufficient for VZV vaccination in patients born before 2005. Neither the vaccination certificate nor the history of chicken pox is reliable to predict VZV immunity indicating a need for serologic investigations and if needed vaccination before initiating immunosuppressive therapy.